Growth hormone receptors in the atherinid Odontesthes bonariensis: Characterization and expression profile after fasting-refeeding and growth hormone administration - Botta, Pablo Eduardo (2016)
In order to improve the understanding of pejerrey Odontesthes bonariensis, growth hormone (Gh)-insulin-like growth factor-1(Igf1) axis, O. bonariensis growth hormone receptor type 1 (ghr1) and type 2 (ghr2) mRNA sequences were obtained. Both transcripts were ubiquitously expressed except in kidney, encephalon and anterior intestine. Alternative transcripts of both receptors were found in muscle. Interestingly, two different ghr2 transcripts with alternative polyadenylation (APA) sites located in the long 3′ untranslated region (UTR-APA) were also found in liver. Hepatic ghr1, ghr2 and insulin-like growth factor type 1 (igf1) transcript levels were examined under two different metabolic conditions. In the first experimental condition, fish were fasted for 2 weeks and then re-fed for another 2 weeks. Despite igf1 mRNA relative expression did not show significant differences under the experimental period of time examined, both ghr transcripts decreased their expression levels after the fasting period and returned to their control levels after re-feeding. In the second treatment, recombinant O. bonariensis growth hormone (r-pjGh) was orally administered once a week. After 4 weeks of treatment, liver igf1, ghr1 and ghr2 mRNA relative expression increased (13, 4·5 and 2·1 fold, P < 0·05) compared to control values. These results add novel information to the growth hormone-insulin-like growth factor system in teleosts.